MTOR signaling intervention by Torin1 and XL388 in the insular cortex alleviates neuropathic pain. (23rd January 2020) - Choi, Songyeon; Kim, Kyeongmin; Cha, Myeounghoon; Kim, Minjee; Lee, Bae Hwan
Highlights: After nerve injury, the phosphorylated mTOR and its downstream effectors increased. Torin1 and XL388 reduced mechanical allodynia in nerve-injured rats. Torin1 and XL388 down regulated phosphorylated mTOR and its substrates, but not Akt. Inhibition of mTORC1 and mTORC2 in the insular cortex attenuated neuropathic pain. Abstract: Signaling by mammalian target of rapamycin (mTOR), a kinase regulator of protein synthesis, has been implicated in the development of chronic pain. The mTOR comprises two distinct protein complexes, mTOR complex 1 (mTORC1) and mTORC2. Although effective inhibitors of mTORC1 and C2 have been developed, studies on the effect of these inhibitors related to pain modulation are still lacking. This study was conducted to determine the inhibitory effects of Torin1 and XL388 in an animal model of neuropathic pain. Seven days after neuropathic surgery, Torin1 or XL388 were microinjected into the insular cortex (IC) of nerve-injured animals and behavioral changes were assessed. Administration of Torin1 or XL388 into the IC significantly increased mechanical thresholds and reduced mechanical allodynia. At the immunoblotting results, Torin1 and XL388 significantly reduced phosphorylation of mTOR, 4E-BP1, p70S6K, and PKCα, without affecting Akt. These results strongly suggest that Torin1 and XL388 may attenuate neuropathic pain via inhibition of mTORC1 and mTORC2 in the IC.